PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA AUDIOVISUAL DALAM PEMBELAJARAN KETERAMPILAN MENYIMAK PEMAHAMAN TEKS EKSPLANASI DI KELAS IX SMP NEGERI 7 PADANG - Aspani, Claudya; Nursaid*, Nursaid; Indriyani, Vivi; Nofrahadi, Nofrahadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) model assisted by audiovisual media in teaching listening comprehension of explanation texts for ninth-grade students at SMP Negeri 7 Padang. The research employed a qualitative descriptive method to explore the stages of planning, implementation, and evaluation of the learning process. Data were collected through observation, interviews, documentation, and field notes. The findings reveal that the learning planning was relatively systematic, including the preparation of teaching modules, audiovisual media, and learning activities based on PBL syntax. The implementation stage showed that students were actively engaged in problem-solving activities through listening to explanation texts presented via audiovisual media. However, some limitations were found, particularly in the lack of detailed assessment rubrics and incomplete learning documents. In the evaluation stage, both process and outcome assessments indicated improved student engagement and better comprehension of explanation texts. Overall, the integration of PBL and audiovisual media contributed positively to supporting students’ listening comprehension, critical thinking, and active participation in learning.